2002
DOI: 10.1002/ar.10108
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in digit‐length ratios of laboratory mice

Abstract: The lengths of the index finger (2D) and ring finger (4D) are sexually dimorphic in humans, and men have a smaller 2D:4D ratio compared to women. Prenatal androgens appear to be important in the development of the 2D:4D sex difference, since it has been reported in children as young as 2 years old, and since humans exposed to supernormal prenatal androgen levels display a smaller 2D:4D ratio. We tested whether another mammalian species in which the process of peripheral sexual differentiation is androgen-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
5
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 18 publications
9
79
5
3
Order By: Relevance
“…Taken together, these two pieces of evidence suggest that the two feet may not be differentially susceptible to androgenization/estrogenization during development. This result, however, differs from previously reported larger sexual dimorphism in 2D:4D of the right compared to the left side in humans and laboratory mice (Manning et al, 1998;Williams et al, 2000;Brown et al, 2002b). …”
Section: Mean (ϩ Se) Length Ratios Of Metatarsals (M) Proximal Phalacontrasting
confidence: 99%
See 2 more Smart Citations
“…Taken together, these two pieces of evidence suggest that the two feet may not be differentially susceptible to androgenization/estrogenization during development. This result, however, differs from previously reported larger sexual dimorphism in 2D:4D of the right compared to the left side in humans and laboratory mice (Manning et al, 1998;Williams et al, 2000;Brown et al, 2002b). …”
Section: Mean (ϩ Se) Length Ratios Of Metatarsals (M) Proximal Phalacontrasting
confidence: 99%
“…The pattern of sexual dimorphism we observed among length ratios computed on digits (excluding metatarsals) is similar to that observed in several studies of undissected hand digits in humans (Manning et al, 1998;McFadden and Shubel, 2002) and in the studies of undissected digits of hind paws of laboratory mice or fore paws of rats published to date (Brown et al, 2002b;Manning et al, 2003;McMechan et al, 2004), suggesting that previous observations of variation in relative length of undissected digits actually reflected length ratios between bones. However, the single existing study of undissected digit ratios in nonhuman primates (Roney et al, 2004) has shown a pattern of sexual dimorphism in digit ratios different from that observed in humans and rodents, suggesting that sexual differences in digit ratios can vary even between closely related species.…”
Section: Mean (ϩ Se) Length Ratios Of Metatarsals (M) Proximal Phalasupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings and the results of other studies on digit lengths and ratios in laboratory rodents [9,11,26,27,45] show this endpoint to be a potentially useful indicator that may be associated with gestational testosterone levels, the testosterone to oestrogen ratio, or prenatal hormonal disruption of the uterine microenvironment. It may indicate hormonal disruptions in response to various types of exposure, e.g.…”
Section: Discussionsupporting
confidence: 68%
“…It has been reported that, in humans, directional asymmetry is grater in males (Williams et al, 2000;Manning, 2002). Evidence for directional asymmetry in the digit ratio has also been shown in mice, where a lower digit ratio in right compared with left limbs was observed (Brown et al, 2002a). In other studies, differences between digit ratios in right and left limbs have been observed, but such evidence is limited (Chang et al, 2008;Rubolini et al, 2006).…”
Section: Introductionmentioning
confidence: 95%